MELACAK BUDAYA PATRIARKI DALAM DRAMA KOSMIK ADAM DAN HAWA: STUDI KOMPARATIF AL-QURAN DAN INJIL - Imam, Muhammad Fuyudun Niam; Prapta, Fico Indra (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
The narrative of Adam and Eve in the sacred texts of the Abrahamic religions (Judaism, Christianity, Islam) has given rise to patriarchal interpretations that portray women (Eve) as inferior beings, the source of sin, and the cause of human downfall. This research aims to trace the roots of patriarchal culture in this narrative and its influence on the formation of theological views and laws that discriminate against women. Using a library research approach and a comparative descriptive method, this study analyzes the narrative of Adam and Eve in the al-Quran, the Book of Genesis, the Gospels, and classical exegetical literature from all three religion traditions. The findings reveal gender-biased interpretations that position Eve as a secondary creature and the cause of humanity's fall, particularly in medieval Christian exegesis. Furthermore, the study identifies the influence of Israelite traditions (Jewish and Christian) that permeated Islamic scholarship, including the patriarchal interpretation of Quranic verses and the formation of Islamic law. This study highlights the urgency of reconstructing interpretations of sacred texts free from gender bias to achieve equality and justice for women across the three Abrahamic religious traditions.